PSYCHOLOGICAL INDEXES AS ACADEMIC SUCCESS PROGNOSTIC CRITERIA FOR STUDENTS IN THE MEDICAL UNIVERSITY - O. V. Toussova; E. R. Isaeva; A. V. Tishkov; A. M. Shaporov; O. V. Pavlova; D. A. Efimov; T. D. Vlasov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Background. This study contributes to theon-going University research of personal characteristics, self-regulation features and professional self-determination among junior medical students in order to develop an effectivecomplex system of psychological support.The purpose of the study was to find psychological criteria that could be significantly prognostic for academic success in the Univercity. Psychodiagnostic tests (Big Five P.Costa, R.McRae; State – Trait AnxietyInvertory, method of V. I. Morosanova, Style of Self-Regulation Test) and special Survey have been used to study professional self-determination, personal characteristics and self-regulationfeatures. Grade Point Average (GPA) for the study duration,calculated as the ratio of the sum of all ratings for number of passed objects, number of sessions without debts and the existence of debts were taken as academic success criteria. Materials and methods. The study involved 697 the 3rd year students of «Pavlov First Saint Petersburg State Medical University». Psychological testing of these students were conducted twice (during the first and the third years of education). The first year psychological test results have been used to search the role of psychological parameters in academic success prognostic criteria.Results. Lower situational anxiety and ability to program, evaluate and plan actions have been found significant in predicting higher grade point average; lower self-regulation of behavior, lower organization, conscientiousness and extraversion – in predicting expulsion from the University. Further development. It is important to use the study results in order to develop programs of psychological support and individual approach to students with lower intellectual and personal resources at the beginning but who still would like to complete education.Conclusions. The received results demonstrate the necessity for further in-depth and consistent study of correlation between psychological variables and academic success, and further search for academic success prognostic criteria.